Religião e Sertão: A Vida, A Palavra e o Sagrado Como Veredas De Leitura Teológicoliterária Para a Obra de João Guimarães Rosa - Silva, Clademilson Fernandes Paulino da (2009)
This present thesis, titled: Religion and Hinterland, is an attempt to read, from the bias of the dialogue between religion, theology and literature, and the correspondence method from Antonio Carlos de Melo Magalhães, the work of the writer from Minas Gerais, João Guimarães Rosa. Thus, the thesis follows by three major matches found not only in Guimarães Rosa work, but also, in a common and constant form, in almost all studies that follow the theology and literature interface: word, life and sacred. Life as the existence process the crossing of the human being, word as the existence manifestation, and sacred as the reason for this existence. Thus, the four chapters of the thesis follow this correspondences: the first chapters with a discussion about the dialogue itself: religion, theology and literature, followed by three others chapters, as paths of reading: life, word and sacred.(AU)